Delph Carpenter, father of Colorado River treaties: text of Governor Ralph L. Carr's 1943 salute to Delph Carpenter - Carr, Ralph L. (Ralph Lawrence), 1887-1950, author; Carpenter, Delph, author; Grigg, Neil S., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1991)
The rulebook for the Colorado River is the 1922 Colorado River Compact, a document now nearly 70 years old. Time said, "This critical document facilitated both the astonishing development of the West and the problems that followed as a result." The centerpiece of Delph Carpenter's career was the Colorado River Compact and the acknowledgement of his role came from no less a person than President Herbert Hoover. Hoover's admiration for the work of Carpenter is evident from the two letters included in the booklet. Not only was Delph Carpenter an institution in the field of western water law; he left a legacy through his son Donald, who became an attorney and accompanied his father to many water meetings including trips to see President Hoover. When Delph Carpenter became disabled with Parkinson's Disease but struggled to continue his work, his son Donald took care of his father's personal needs while he continued to work on the interstate water treaties. At the time that Governor Ralph Carr delivered the speech which is reprinted here, Donald was on the East Coast awaiting shipment to Europe in World War II. Ex-President Hoover arranged for Donald to attend the banquet. Donald Carpenter went on to a distinguished career as a district judge in Greeley, including presiding over the water court. Today's students of water resources management will benefit from the study of this speech and the vision held by Delph Carpenter and his peers about Western water management.
September 1991.
Includes introductory material, text of Colorado River Compact.
Keywords: Carpenter, Delph; United States. Bureau of Reclamation; Water resources development -- Colorado River (Colo.-Mexico); Water transfer -- Colorado; Colorado River (Colo.-Mexico)